2020
DOI: 10.1101/2020.11.13.381533
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Molecular basis for a germline-biased neutralizing antibody response to SARS-CoV-2

Abstract: The SARS-CoV-2 viral spike (S) protein mediates attachment and entry into host cells and is a major target of vaccine and drug design. Potent SARS-CoV-2 neutralizing antibodies derived from closely related antibody heavy chain genes (IGHV3-53 or 3-66) have been isolated from multiple COVID-19 convalescent individuals. These usually contain minimal somatic mutations and bind the S receptor-binding domain (RBD) to interfere with attachment to the cellular receptor angiotensin-converting enzyme 2 (ACE2). We used … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 46 publications
3
23
0
Order By: Relevance
“…Additional common SHMs among IGHV3-53/3-66 RBD antibodies with a short CDR H3 include S31R in CDR H1 and V50L in CDR H2 (Figure 5a). As a result, while IGHV3-53/3-66 RBD antibodies do not require any SHM to neutralize SARS-CoV-2 57 , this study along with others have shown that SHM can substantially improve the binding affinity of IGHV3-53/3-66 antibodies to RBD 38,57 . Consistently, RBD antibodies from convalescent SARS-CoV-2 patients have significantly more SHMs and higher neutralization potency at 6 months postinfection than at 1-month post-infection 62 .…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Additional common SHMs among IGHV3-53/3-66 RBD antibodies with a short CDR H3 include S31R in CDR H1 and V50L in CDR H2 (Figure 5a). As a result, while IGHV3-53/3-66 RBD antibodies do not require any SHM to neutralize SARS-CoV-2 57 , this study along with others have shown that SHM can substantially improve the binding affinity of IGHV3-53/3-66 antibodies to RBD 38,57 . Consistently, RBD antibodies from convalescent SARS-CoV-2 patients have significantly more SHMs and higher neutralization potency at 6 months postinfection than at 1-month post-infection 62 .…”
Section: Discussionsupporting
confidence: 51%
“…Interestingly, a Y58F mutation results in a loss of hydrogen bonding interactions between residue 58 of the heavy chain and T415 of the RBD ( Supplementary Figure 10), yet the mutation significantly increases the binding affinity of the antibody to the RBD. We then performed a structural analysis on seven IGHV3-53/66 RBD antibodies with Y58F mutation and nine without 26,29,38,40,47,[54][55][56][57] . Our results indicate that, by removal of the hydroxyl group, the side chain of Y58F moves closer to the backbone carbon of RBD T415 (Supplementary Figure 10).…”
Section: Y58f Is a Signature Shm In Ighv3-53/3-66 Rbd Antibodiesmentioning
confidence: 99%
“…43 The mutations on the RBD are considered for the predictions of BFE changes. Our predictions are built from the X-ray crystal structure of SARS-CoV-2 S protein and ACE2 (PDB 6M0J), 57 76 and 7KFY 76 ). The BFE change following mutation (DDG) is dened as the subtraction of the BFE of the mutant type from the BFE of the wild type: DDG ¼ DG W À DG M , where DG W is the BFE of the wild type and DG M is the BFE of the mutant.…”
Section: Mutation Impacts On Sars-cov-2 Antibodiesmentioning
confidence: 99%
“…E484 (left) and K417 (right) are represented by red and blue spheres, respectively, and are also labeled in the first panel. All available RBD-targeting IGHV3- 53/3-66 antibody structures in the PDB at time of analysis (January 2021) are shown: CC12.1 (PDB ID: 6XC3), CC12.3 (PDB ID: 6XC4) ( 20 ), COVA2-04 (PDB ID: 7JMO) ( 21 ), B38 (PDB ID: 7BZ5) ( 22 ), CB6 (PDB ID: 7C01) ( 23 ), CV30 (PDB ID: 6XE1) ( 24 ), C105 (PDB ID: 6XCN) ( 25 ), BD-236 (PDB ID: 7CHB), BD-604 (PDB ID: 7CH4), BD-629 (PDB ID: 7CH5) ( 26 ), C102 (PDB ID: 7K8M) ( 27 ), C1A-B3 (PDB ID: 7KFW), C1A-C2 (PDB ID: 7KFX), C1A-B12 (PDB ID: 7KFV), C1A-F10 (PDB ID: 7KFY) ( 28 ), P4A1 (PDB ID: 7JCF) ( 29 ), COVA2-39 (PDB ID: 7JMP) ( 21 ), and C144 (PDB ID: 7K90) ( 25 ).…”
Section: Supplementary Figurementioning
confidence: 99%
“…Previously, we and others demonstrated that IGHV3-53/3-66 RBD antibodies can adopt two different binding modes ( 44, 46 ), which we now refer to as binding modes 1 and 2, with distinct epitopes and angles of approach to the receptor binding site (RBS) (Figure 2B, Figure S3). All known IGHV3-53/3-66 RBD antibodies with binding mode 1 have a short CDR H3 of < 15 amino acids and bind to the RBS-A epitope ( 11, 15, 31 ), while those with binding mode 2 contain a longer CDR H3 (≥ 15 amino acids) and target RBS-B ( 44, 46, 47 ). These dual binding modes enhance the recognition potential of this antibody family for the SARS-CoV-2 RBD, although 16 of 18 IGHV3-53/3-66 RBD antibodies with structural information adopt binding mode 1 (Figure S3).…”
Section: Introductionmentioning
confidence: 99%